Achieving High Stability and Rate Performance Using Spherical Nickel-Zinc Layered Double Hydroxide in Alkaline Solution. Issue 7 (20th July 2021) - Qin, Runyue; Pan, Yunpeng; Duan, Zeang; Su, Huanhuan; Ren, Kailiang; Wang, Wenfeng; Li, Yuan; Xi, Ning; Wang, Yu; Zhang, Lu; Han, Shumin
Abstract : Nickel layered double hydroxide, Ni(OH)2, has been widely used as the cathode for nickel based battery systems. However, the currently commercialized β -Ni(OH)2 is limited by its low capacity. In contrast, α -Ni(OH)2 can give higher capacity, but it is challenging to stabilize in alkaline solution due to the conversion to β -Ni(OH)2 . Herein, we use zinc doped Ni(OH)2 and control its spherical morphology to strengthen the stability of α -Ni(OH)2 in a nickel metal hydride battery system. With an optimal zinc doping content of 3 mol% for the spherical α -Ni(OH)2 (Ni-Zn3), the cathode shows the highest discharge capacity of 351.3 mAh g –1 at a current density of 70 mA g –1 (0.2 C) and superior rate performance, which even delivers 271.5 mAh g –1 at 5 C. More importantly, the durability of the Ni-Zn3 cathode is significantly enhanced, which maintains 81.7% after cycling 360 times, almost twice as long as that of pure α -Ni(OH)2 . Studies show that the stabilized Ni–O bond and suitable aperture structure are mainly responsible for the advanced electrochemical properties of the Ni-Zn3. The results show that proper zinc doping spherical α -Ni(OH)2 with low-cost and high performance is an promising cathode material for nickel-based battery systems.